Hemp seed significantly modulates the endocannabinoidome and produces beneficial metabolic effects with improved intestinal barrier function and decreased inflammation in mice under a high-fat, high-sucrose diet as compared with linseed - Ben Necib, Rim; Manca, Claudia; Lacroix, Sébastien; Martin, Cyril; Flamand, Nicolas; Di Marzo, Vincenzo; Silvestri, Cristoforo (Frontiers in Immunology, 2022)
Omega-3 fatty acids support cardiometabolic health and reduce chronic low-grade inflammation. These fatty acids may impart their health benefits partly by modulating the endocannabinoidome and the gut microbiome, both of which are key regulators of metabolism and the inflammatory response. Whole hemp seeds (Cannabis sativa) are of exceptional nutritional value, being rich in omega-3 fatty acids. We assessed the effects of dietary substitution (equivalent to about 2 tablespoons of seeds a day for humans) of whole hemp seeds in comparison with whole linseeds in a diet-induced obesity mouse model and determined their effects on obesity and the gut microbiome-endocannabinoidome axis. We show that whole hemp seed substitution did not affect weigh gain, adiposity, or food intake, whereas linseed substitution did, in association with higher fasting glucose levels, greater insulin release during an oral glucose tolerance test, and higher levels of liver triglycerides than controls. Furthermore, hemp seed substitution mitigated diet-induced obesity-associated increases in intestinal permeability and circulating PAI-1 levels, while having no effects on markers of inflammation in epididymal adipose tissue, which were, however, increased in mice fed linseeds. Both hemp seeds and linseeds were able to modify the expression of several endocannabinoidome genes and markedly increased the levels of several omega-3 fatty acid–derived endocannabinoidome bioactive lipids with previously suggested anti-inflammatory actions in a tissue specific manner, despite the relatively low level of seed substitution. While neither diet markedly modified the gut microbiome, mice on the hemp seed diet had higher abundance of Clostridiaceae 1 and Rikenellaceae than mice fed linseed or control diet, respectively. Thus, hemp seed-containing foods might represent a source of healthy fats that are not likely to exacerbate the metabolic consequences of obesogenic diets while producing intestinal permeability protective effects and some anti-inflammatory actions.